The impact of internal audits on an internal quality management system in Higher Education in Portugal - Jesus-Silva, Natacha (2020)
Currently, the growing and increasingly demanding needs of the Higher Education, internally and externally, make Higher Education Institutions reach high levels of organizational complexity, structure and information. The internal audit appears as an important instrument to support management. This should be understood as the control of controls, with the aim of providing the higher education institution a reliability assessment of the internal control system. The aim of the internal audit is to determine if the procedures are adequate and meet the needs of the institution. If, and when, necessary recommendations shall be made in order to fill the identified gaps hence assuring the protection and optimization of the Institution and available resources. Internal audits are a primary tool for monitoring and quality assurance. These must be carried out with due formalism, that is, the audit teams must, as a matter of principle, know the Internal Quality Assurance System (IQAS) making use of appropriate mechanisms and recording. In order to guarantee the continuous improvement of the system, internal audits must be carried out at various times during the school year, and not just at a single moment. There are several instruments that may be used to control the Internal Quality Assurance System, with the goal to simplify the overall internal audits, assuring a solid, non biased, evidence based assessment of the institution performance. The function of inspecting and surveilling the compliance with the institution's internal rules is outdated. It is, instead, the most appropriate means of assuring the continuous improvement of an Internal Quality Assurance System.